The Coronavirus Era and its new vocabulary and phraseology in Slavic languages - Danylenko, Liudmyla (Slavia Centralis, 2022)
The purpose of this research is to study new vocabulary and phraseology that appeared in relation to the coronavirus pandemic in different groups of Slavic languages: Ukrainian, Russian and Czech. Thematic groups, figurative and word-shaping resources are described. The results of the research revealed parallel trends: Mainly borrowings from the English language and occasional neologisms with a clear expressive tone. Innovations in the fields of Phraseology and Paremiology take place based on the existing structural-semantic models and transformations of proverbs into new anti-proverbs.
Keywords: neologisms; coronavirus; semantics; word-formation processes; vocabulary; phraseology; Ukranian; Russian; Czech languages